Implementasi Prinsip Etika Bisnis Islam dalam Transaksi Jual Beli pada Pasar Tuasan Kota Medan - Hayati, Fitri; Fikri, Tyo Azharil; Yahman, Qaila Nailaya; Anggina, Ita Ayu; Fadilah, Cut (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study discusses the implementation of Islamic business ethics principles in buying and selling transactions at Pasar Tuasan, Medan City. Buying and selling transacti ons are essential activities to meet daily needs. Pasar Tuasan serves as a place for social interaction and meetings between sellers and buyers. However, rapid economic development has led to unhealthy business competition, characterized by deceptive practices that harm consumers. Therefore, the application of Islamic business ethics is crucial to maintaining honesty and transparency in transactions. This research employs observation and interviews to collect data from grocery traders at Pasar Tuasan. The findings indicate that while some traders have implemented Islamic business ethics principles, there are still shortcomings in terms of openness regarding the quality of goods sold. This study aims to reveal how buying and selling transactions should be conducted in accordance with Islamic business ethics.